Process enhancement and performance evaluation of single‑shot drilling of CFRP/aluminum stacks: a review - Joy Mathavan, J.; Hassan, Muhammad Hafiz (The International Journal of Advanced Manufacturing Technology, 2025)
Drilling is an essential process in the construction of aircraft panels made from composite/metal stack materials, and it has a considerable impact on the performance of the aircraft during flight and its overall lifespan. Among CFRP/Al/Ti, CFRP/ Ti, and CFRP/Al stacks, CFRP/Al panels are widely used in the aviation industry. This paper examines in detail the develop ments made in the drilling of stacks made of carbon fiber reinforced polymer (CFRP) and aluminum (Al), with the goal of determining how different machining parameters affect the quality of the holes. The primary requirements for aircraft com ponents are to attain a low level of hole surface roughness, minimize burr heights, reduce the diameter difference in stack-up, and minimize delamination. The subject matter encompasses a wide range of tool shapes, materials, drilling parameters, and innovative methods of cooling and coating, all with the goal of reducing hole damage and improving quality. In addition, the paper examines several forms of hole damage and presents modern methodologies for their quantification. This review study aims to develop a reliable standard for achieving accuracy, optimal productivity, and reducing harm in the drilling procedure of CFRP/Al stacks in aerospace applications. Future works on analysis of bond strength, hardness, and coefficient of friction of coated drill bits and application of nano fluid-based coolants may further enhance the drilling quality
Keywords: CFRP/Al stack; Machining; Surface analysis; Damage tolerance